Optical Properties of the Self-Assembling Polymeric Colloidal Systems. (1st September 2013) - Mocanu, Alexandra; Rusen, Edina; Diacon, Aurel
Abstract : In the last decade, optical materials have gained much interest due to the high number of possible applications involving path or intensity control and filtering of light. The continuous emerging technology in the field of electrooptical devices or medical applications allowed the development of new innovative cost effective processes to obtain optical materials suited for future applications such as hybrid/polymeric solar cells, lasers, polymeric optical fibers, and chemo- and biosensing devices. Considering the above, the aim of this review is to present recent studies in the field of photonic crystals involving the use of polymeric materials.